Surgical aspect of patient care with cleidocranial dysplasia - case report - Szczepkowska, Aleksandra; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2016)
The work shows a case of the first stage of orthodontic-surgical treatment 16-year-old patient suffering with cleidocranial dysplasia, which was carried out under general anesthesia.